PENDAMPINGAN PENGENALAN DASAR KOMPUTER BAGI ANAK USIA DINI DI TK AL-AMIN KECAMATAN NGAMPRAH BANDUNG BARAT - Tati Ernawati; Ade Rizki; Naufal Nafi Dzimar; Mamay Syani; Budi Upayarto (ASOSIASI IDEBAHASA KEPRI, 2026)
Early Childhood Education plays a highly strategic role in preparing children holistically, including in building their readiness for the digital age. However, the reality on the ground shows that most students at Al-Amin Kindergarten in Ngamprah, West Bandung Regency, have never received basic computer instruction. This study aims to provide computer introduction guidance to early childhood students through the application of the storytelling method, presented in the form of a picture book titled “Dino Learns Computers.” This Community Service activity was attended by 22 students; the material covered included an introduction to computer hardware components, how to type, guidelines for responsible computer use, and the moral lessons contained in the story. Evaluation was conducted through a quiz session at the end of the activity. The results of the activity showed an increase in students’ understanding of basic computer introduction material, as evidenced by high enthusiasm, student engagement in responding to questions, and the courage to ask questions. The application of the storytelling method proved effective in creating a fun, interactive learning atmosphere aligned with the cognitive development stage of early childhood, thereby allowing the material to be conveyed more naturally and easily understood. This activity is recommended for further development through advanced training programs and the development of learning media